2005
DOI: 10.1016/j.trstmh.2004.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Regression of hepatosplenomegaly in Kenyan school-aged children after praziquantel treatment and three years of greatly reduced exposure to Schistosoma mansoni

Abstract: Evaluating regression of morbidity associated with parasitic infections is an important component of community-based control programmes. We performed an intervention against Schistosoma mansoni infection, focusing on hepatosplenomegaly in the absence of periportal fibrosis, in a cohort of 67 Kenyan children aged 7-18 years from Makueni District, selected on the basis of hepatosplenomegaly detected by ultrasonography. Clinical and ultrasound examinations were conducted annually for three years after treatment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…The ACR metric may provide a more direct quantification of pathognomonic signs (as evidenced by the children shown in Figure 2) and enables convenient comparison between children. In accordance with recent findings (Vennervald et al, 2005), a high proportion (67.8%) of the children in our sample had firm and >1 cm enlarged livers and spleens, with several showing surprisingly advanced liver fibrosis on ultrasound. Although the distribution of the ACRs across the sample appeared normal (see Figure 3), further analysis of ACR scores revealed geographic overdispersion within Bugiri, Hoima and Mayuge districts and pinpointed several schools where morbidity appeared much elevated (Figure 4).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The ACR metric may provide a more direct quantification of pathognomonic signs (as evidenced by the children shown in Figure 2) and enables convenient comparison between children. In accordance with recent findings (Vennervald et al, 2005), a high proportion (67.8%) of the children in our sample had firm and >1 cm enlarged livers and spleens, with several showing surprisingly advanced liver fibrosis on ultrasound. Although the distribution of the ACRs across the sample appeared normal (see Figure 3), further analysis of ACR scores revealed geographic overdispersion within Bugiri, Hoima and Mayuge districts and pinpointed several schools where morbidity appeared much elevated (Figure 4).…”
Section: Discussionsupporting
confidence: 93%
“…A negative correlation between the change in ACR (ACR 1 − ACR 0 ) and the mean of the two ACR values (0.5[ACR 0 + ACR 1 ]) showed a tendency of higher mean ACR scores by school to show a larger decrease than those with lower mean ACR scores. The ameliorative effect of treatment on reduction of organomegaly is well known (Boisier et al, 1998;Vennervald et al, 2005). However, regression towards the mean can also be a general statistical phenomenon of a reduced sample size.…”
Section: Discussionmentioning
confidence: 99%
“…7,36 However, 39.4% of children had liver pattern B, indicative of early signs of morbidity. Following treatment, the prevalence of liver pattern B decreased significantly.…”
Section: Clinical Morbiditymentioning
confidence: 99%
“…Clinical trials have demonstrated that praziquantel is a safe and efficacious treatment against both species, and that repeated chemotherapy decreases infection and related morbidity. [1][2][3][4][5][6][7] One of the main control methods is treating schoolchildren with praziquantel together with albendazole as part of school health programmes. As this method uses the existing school infrastructure and provides easy accessibility to children, it is a cost-effective public health strategy, 8 and many pilot programmes have demonstrated its feasibility, affordability and effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…16 Currently, the WHO strategy for schistosomiasis control relies on mass-drug administration (MDA) of praziquantel, 17 which is effective in reducing disease-associated morbidity. [18][19][20][21][22] The impact of MDA is measured by a change in infection prevalence and intensity. Guidelines exist for schistosomiasis MDA thresholds, frequency, and target populations (school-based versus community-wide), but there are few objective data supporting them.…”
Section: Introductionmentioning
confidence: 99%